Do patient decision aids help people who are facing decisions about solid organ transplantation? A systematic review. Issue 4 (19th February 2023) - Irish, Georgina L.; Weightman, Alison; Hersch, Jolyn; Coates, P. Toby; Clayton, Philip A
Abstract: Background: Decisions about solid organ transplantation are complex. Patient decision aids (PDAs) enhance traditional education, by improving knowledge and supporting patients to align their values with treatments. There are increasing numbers of transplantation PDAs, however, it is unclear whether these are effective. We conducted a systematic review of studies assessing the impact of PDA use in transplantation. Methods: We searched the Cochrane Register of Controlled Trials, CINAHL, EMBASE, MEDLINE, and PsycINFO databases from database inception to October 26, 2020. We included primary studies of solid organ transplantation PDAs defined by the International Patient Decision Aids Standards. All comparators and reported outcomes were included. Mean difference in knowledge (before vs. after) was standardized on a 100‐point scale. Pooled‐effect for PDAs was calculated and compared to the standard of care for randomized controlled trials (RCTs) and meta‐analyzed using random effects. Analysis of all other outcomes was limited due to heterogeneity (PROSPERO registration, CRD42020215940). Results: Seven thousand four hundred and sixty‐three studies were screened, 163 underwent full‐text review, and 15 studies with 4278 participants were included. Nine studies were RCTs. Seven RCTs assessed knowledge; all demonstrated increased knowledge with PDA use (mean difference, 8.01;95%CI 4.69–11.34, p < .00001). There were many other outcomes, including behavior and acceptability, but these were too heterogenous and infrequently assessed for meaningful synthesis. Conclusions: This review found that PDAs increase knowledge compared to standard education, though the effect size is small. PDAs are mostly considered acceptable; however, it is difficult to determine whether they improve other decision‐making components due to the limited evidence about non‐knowledge‐based outcomes.